ABON IKAN LELE: PROGRAM KKN TEMATIK DESA NGESREP UNTUK PENGUATAN POTENSI LOKAL DAN KEMANDIRIAN PANGAN - Egytias, Aik Fiermar; Zahidah, Nabila Nada Shofa Az; Rachma, Ardhy Avrina; Priadythama, Ilham (MAJU : Indonesian Journal of Community Empowerment, 2025)
The KKN is a form of student dedication to society through the application of academic knowledge. The socialization and demonstration program on catfish floss production was conducted in Ngesrep Village, Ngemplak Sub-district, Boyolali Regency, in July-August 2025. The aim was to enhance community knowledge and skills in food diversification using catfish and to encourage the development of new business opportunities.The methods included a local potential survey, counseling on the benefits of food diversification, hands-on practice of catfish floss making, and evaluation of community participation. An economic calculation indicated that 1 kg of fresh catfish yields about 250 g of floss with resulting in a net profit of Rp13,000/kg. Thus, the community not only acquired new skills but also discovered business opportunities that could strengthen the local economy.